Unlocking the Power of Electrospinning: A Review of Cutting-Edge Polymers and their Impact on Scaffold Design and Performance - Nemade, Aditya; Ghosh, Tanmoy; Vineeth Kumar K.2; Shruthi, N.; Shwetha, V.; Pushpalatha, C. (Current Drug Delivery, 2025)
Electrospun scaffolds are pivotal in tissue engineering due to their ability to mimic the Extracellular Matrix (ECM). Despite their potential, challenges such as, two-dimensional structure, limited load bearing capacity, and low mechanical strength restrict their application. This review explores advancements in electrospinning techniques and materials, highlighting methods like coaxial electrospinning, which enables the encapsulation of therapeutic agents, and the integration with 3D printing to create hybrid scaffolds with improved cell infiltration. Characterization techniques assessed by different researchers, such as scaffold morphology, mechanical properties, and biocompatibility, show that scaffolds with high spatial interconnectivity and controlled alignment enhance cell orientation and migration. Innovations in smart polymers and stimuli-responsive materials have furthered scaffold functionality. While recent advancements address some limitations, issues with scalability and production uniformity remain. Future research should optimize fabrication parameters and explore novel materials to enhance scaffold performance, requiring collaborative efforts and technological innovations to expand their practical applications in tissue engineering and regenerative medicine.
Keywords: Electrospun scaffolds